Doktrin balasan : undang-undang perbandingan antara Inggeris, Malaysia, India, dan Islam - Tamjes Kastiran , 1943- (Universiti Teknologi Malaysia, 1990)
Doctrine of consideration of the law of contract; comparative study of English, Malaysian, Indian, and Islamic law